Fast Evaluation of the Caputo Fractional Derivative and its Applications to Fractional Diffusion Equations. (7th February 2017) - Jiang, Shidong; Zhang, Jiwei; Zhang, Qian; Zhang, Zhimin
Abstract: The computational work and storage of numerically solving the time fractional PDEs are generally huge for the traditional direct methods since they require total memory and work, where NT and NS represent the total number of time steps and grid points in space, respectively. To overcome this difficulty, we present an efficient algorithm for the evaluation of the Caputo fractional derivative of order α ∈(0, 1). The algorithm is based on an efficient sum-of-exponentials (SOE) approximation for the kernel t –1– α on the interval [Δ t, T ] with a uniform absolute error ε . We give the theoretical analysis to show that the number of exponentials N exp needed is of order for T ≫1 or for T H1 for fixed accuracy ε . The resulting algorithm requires only storage and work when numerically solving the time fractional PDEs. Furthermore, we also give the stability and error analysis of the new scheme, and present several numerical examples to demonstrate the performance of our scheme.